Introduction (Scottish Archaeological Internet Reports, 2018)
Lead ore (galena) had been extracted from the site of Siller Holes, West Linton, from medieval times if notearlier; there, according to tradition, silver was refined from the lead (Pb). Creation of a pond at the footof Lead Law produced large quantities of textiles, leather and pottery which could be dated to the 12thto 14th centuries; lead, slag and ore were also recovered. As there is no documented reference to the siteuntil the late 16th century, it has not yet been established who was exploiting the minerals.